Enhancement of Latent Inhibition by Chronic Mild Stress in Rats Submitted to Emotional Response Conditioning - Liana Lins Melo; Elenice A. de Moraes Ferrari; Nancy Airoldi Teixeira; Guy Sandner (Neural Plasticity)
This work evaluated the influence of chronic mild stress on latent inhibition (LI) in rats, using a conditioned emotional response (CER) procedure. Rats were assigned to four groups: a non pre-exposed control group (NPC), a non pre-exposed stressed group (NPS), a preexposed control group (PC), and a pre-exposed stressed group (PS). Stressed animals were submitted to a chronic mild stress (CMS) regimen for three weeks. The off-baseline conditioned emotional response procedure had four phases: licking response training, tone- shock conditioning, retraining, and testing. Conditioning consisted of 2 tone (30 s) and shock (0.5 s) associations. Tone-shock conditioning evidenced by NPS and NPC groups suggests that stress did not interfere with the expression of a conditioned emotional response. Pre-exposure was carried out using 6 tones (30 s) during 2 sessions before conditioning. Prior exposure to the tone resulted in a decrease in learning that was greater in stressed animals. The results indicate an increase in latent inhibition induced by chronic mild stress. Such LI potentiation after CMS may be related to dopamine (DA) neurotransmission reduction in the central nervous system.